The distal classification and management of choledochal cyst in adults: Based on the relation between cyst and pancreatic duct. Issue 12 (March 2017) - Liu, Yanfeng; Sun, Jingxian; Guo, Sen; Liu, Zengli; Zhu, Min; Zhang, Zong-li
Abstract : Abstract: Todani classification is extensively used to guide the surgical strategy of choledochal cysts, but no systematic investigations on the distal management of intrapancreatic choledochal cysts have been conducted. This study reports the distal classification and management of choledochal cysts in adults based on the relation between the cyst and pancreatic duct. Patients with choledochal cyst who underwent operation, including distal management, in our department from January 2009 to December 2014 were retrospectively reviewed. Patients presenting symptoms, coexisting diseases, surgical treatment, perioperative complications, and long-term follow-up according to the distal classification of choledochal cyst were analyzed. A total of 54 patients with choledochal cyst were included in the present retrospective study. Based on the distal classification of choledochal cyst, 39 patients (72.22%) were type 1, 13 patients (24.07%) were type 2, and 2 patients (3.70%) were type 3. Thirty-nine type 1 patients and 10 type 2 patients underwent excision of intrapancreatic choledochal cyst or bile duct. Three type 2 patients received excision of distal cylindrical cyst and papilla, followed by pancreatic duct plasty with duodenum mucosa. One type 3 patient underwent endoscopic sphincteroplasty, and another type 3 patient underwent transduodenal sphincteroplasty. After the operation, 11 patients (20.37%, 11/54) had short-term perioperative complications. The long-term follow-up results showed that the satisfactory rate (excellent and good outcomes) was 95.83%. Current distal classification of choledochal cysts could provide a more targeted strategy for complete excision to eliminate potential dead space within the pancreas, protect the pancreatic duct, and prevent reoperation.